Volume 4: Fatigue and Fracture, Heat Transfer, Internal Combustion Engines, Manufacturing, and Technology and Society 2006
DOI: 10.1115/esda2006-95037
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Single and Multiple Impinging Jet Cooling and Comparison With Experimental Data

Abstract: A number of turbulence models offered by the commercial code STAR-CD have been tested on the measurements published in the literature with the objective to compare their capabilities for the simulation of a flow and heat transfer in multiple impinging jets. Numerical predictions of the single jet and jet array air impinging heat transfer have been compared with experimental data. The comparison shows that only turbulence models with additional limiters for turbulence production in the stagnation zone are able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, it is expected that the -RNG model gives better results in the regions of the flow where the mean strain rates are high. The performance of the -RNG model of turbulence has been investigated by Knowles and Saddington [11], Gordeev et al [12], Sharif and Mothe [13], Fernández et al [14], Chen [15], Liakos et al [16,17] and Sharif and Mothe [18] in jet flows and all confirmed that the -RNG model can be successfully used to model this type of flows. The -RNG model is numerically robust and faster than the triple transport model and has minimum turn-over time requirements for the calculations [17].…”
Section: Cfd Modeling Strategy Turbulence Model and Numericalmentioning
confidence: 51%
“…Therefore, it is expected that the -RNG model gives better results in the regions of the flow where the mean strain rates are high. The performance of the -RNG model of turbulence has been investigated by Knowles and Saddington [11], Gordeev et al [12], Sharif and Mothe [13], Fernández et al [14], Chen [15], Liakos et al [16,17] and Sharif and Mothe [18] in jet flows and all confirmed that the -RNG model can be successfully used to model this type of flows. The -RNG model is numerically robust and faster than the triple transport model and has minimum turn-over time requirements for the calculations [17].…”
Section: Cfd Modeling Strategy Turbulence Model and Numericalmentioning
confidence: 51%